The Effectiveness of Utilizing Artificial in Telligence (AI) Chatbot REPENA (Teens Care For Disaster) In Disaster Education in The Era of Industrial Revolution 4.0 and Society 5.0 in 2023 - Lisni, Isra Hayati Oktavia; Yanti, Nova (POLTEKKES KEMENKES PADANG, 2024)
Indonesia is a country with the second highest potential for natural disasters in the world (IRBI, 2022). The high potential for disasters in Indonesia is apparently not accompanied by Indonesia's ability to face disasters. So inclusive disaster management is needed, namely disaster management that involves all elements of society, including youth groups. Teenagers who live in the era of industrial revolution 4.0 certainly find it easier to obtain information related to disasters by using technology. For example, in the use of artificial intelligence (AI) technology as a means of education, business, trade (buying and selling) and use of services. Therefore, the author was encouraged to create the REPENA Chatbot as a means of increasing knowledge among teenagers by utilizing Artificial Intelligence (AI) technology. The aim of this research is to find out the effectiveness of using Artificial Intelligence (AI) Chatbot REPENA (Teenagers Care for Disasters) technology in Disaster Education among Class Quasi experimental pre post test method with control group with a sample size of 62 people. Statistical test results show that there is a difference in the average knowledge of students who received education with the REPENA Chatbot with a P Value of 0.025. From the results of this research, it can be concluded that increasing knowledge related to disaster education among teenagers using the REPENA Chatbot is effective and has the potential for great long-term benefits